Health and well-being at work: a survey of employees - Young, Viv; Bhaumik, Claire (London, 2011)
"Health and Well-being at work, a survey of employees was jointly funded by the Health and Safety Executive and the Cross-Government Health, Work and Well-being Strategy Unit. A survey of 2,019 employees, aged 16 +, was conducted between October and December 2009. The survey objectives were to: Develop the evidence base around work and health and workplace health initiatives from the employee perspective. Provide baseline data so that progress on health and well-being at work can be measured and monitored over time."